The World Health Organization Measles Programmatic Risk Assessment Tool—Pilot Testing in India, 2014. Issue 6 (18th April 2016) - Goel, Kapil; Naithani, Saroj; Bhatt, Dheeraj; Khera, Ajay; Sharapov, Umid M.; Kriss, Jennifer L.; Goodson, James L.; Laserson, Kayla F.; Goel, Parul; Kumar, R. Mohan; Chauhan, L. S.
Abstract : Measles is a leading cause of child mortality, and reduction of child mortality is a key Millennium Development Goal. In 2014, the World Health Organization and the U.S. Centers for Disease Control and Prevention developed a measles programmatic risk assessment tool to support country measles elimination efforts. The tool was pilot tested in the State of Uttarakhand in August 2014 to assess its utility in India. The tool assessed measles risk for the 13 districts of Uttarakhand as a function of indicator scores in four categories: population immunity, surveillance quality, program delivery performance, and threat. The highest potential overall score was 100. Scores from each category were totaled to assign an overall risk score for each district. From this risk score, districts were categorized as low, medium, high, or very high risk. Of the 13 districts in Uttarakhand in 2014, the tool classified one district (Haridwar) as very high risk and three districts (Almora, Champawat, and Pauri Garhwal) as high risk. The measles risk in these four districts was largely due to low population immunity from high MCV1–MCV2 drop‐out rates, low MCV1 and MCV2 coverage, and the lack of a supplementary immunization activity (SIA) within the past three years. This tool can be used to support measles elimination in India by identifying districts that might be at risk for measles outbreaks, and to guide risk mitigation efforts, including strengthening routine immunization services and implementing SIAs.